FORMULASI DAN UJI KELEMBAPAN HAND BODY LOTION EKSTRAK ETANOL KULIT PEPAYA (Carica papaya L.): Formulation And Moisture Test Of Hand Body Lotion From Ethanol Extract Of Papaya Peel (Carica Papaya L.) - Fayza Mahadhiti; Ade Maria Ulfa; Vito Zhafran Octonariz (JFL : Jurnal Farmasi Lampung, 2026)
Papaya peel (Carica papaya L.) can be used as a natural cosmetic ingredient because it contains flavonoids that provide skin moisturizing effects. This study aimed to formulate and evaluate the effectiveness of a hand body lotion containing ethanol extract of papaya peel as a skin moisturizer. Formulations were prepared at 2%, 4%, and 6%. The extraction process used the percolation method with 70% ethanol as the solvent, yielding of 51.7%. The lotion was evaluated using physical tests, cream-type tests, irritation tests, occlusivity tests, and clinical moisturization tests. All formulations met the physical parameter requirements. The moisturizing test was conducted clinically on volunteers to assess on skin hydration levels. The most effective moisturizing effect among the three formulations was observed with formulation 3, containing 6% extract concentration, which showed a 35.30% increase in skin moisture after 28 days of application, indicating optimal performance. Therefore, the higher the concentration of papaya peel extract, the greater the increase in skin moisture. The conclution of this study is ethanol extract of papaya peel is effective when formulated into a hand body lotion and can significantly improve skin hydration. Keywords: Formulation, Hand Body Lotion, Moisture, Papaya Peel